Preexisting Chronic Thromboembolic Pulmonary Hypertension in Acute Pulmonary Embolism? A Case Report and Discussion - Lang, Irene M.; Delcroix, Marion (Hämostaseologie, 2023)
A 61-year-old male presented with New York Heart Association class II breathlessness. Three years earlier, he had presented with a swollen leg, had received a diagnosis of deep vein thrombosis on ultrasound and of low-risk acute pulmonary embolism, and had been discharged on a direct oral anticoagulant after 8 hours. The patient also had a history of thyroidectomy and was on levothyroxine substitution. The case illustrates a patient with acute pulmonary embolism who developed chronic thrombotic pulmonary vascular lesions within 3 years after acute pulmonary embolism in the presence of typical risk factors.
Keywords: chronic thromboembolic pulmonary hypertension; multidisciplinary team discussion; thyroidectomy